Depression and aggressiveness in resilient fifth-grade students of secondary school, Rímac-2017 - Flores Morales, Jorge Alberto (2019)
The objective of this research was to determine the causal relationship between depression and aggressiveness in resilient fifth-grade students of secondary school in the district of Rímac, 2017. This was basic research, of non-experimental and cross-sectional design, and causal explanatory level, within a quantitative approach. The sample was of 144 female students. The research concluded that there is a greater relationship between depression and resilience. The significance rates found in the linear regression model were significant, with a lower rate than the one proposed as a decision rule (p <005), therefore the null hypothesis is rejected and the researcher’s one is accepted: The greater the resilience, the lower the depression and aggressiveness will fifth-grade students of secondary school, 2017-Rímac.